KOTAK SAMPAH PINTAR RANCANG BANGUN TEMPAT SAMPAH PINTAR BERBASIS IOT (DESIGN SMART GARBAGE BASED IOT) PADA PDAM WAY KOMERING, MARTAPURA, SUMATRA SELATAN: RANCANG BANGUN TEMPAT SAMPAH PINTAR BERBASIS IOT (DESIGN SMART GARBAGE BASED IOT) PADA PDAM WAY KOMERING, MARTAPURA, SUMATRA SELATAN - Eko Win Kenali; Wijaya, Fidi Fran; Asrowardi, Imam (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2023)
Currently, Indonesia is experiencing a waste emergency and it is very worrying. The amount of waste generated by the population in Indonesia reaches 189 thousand tons per day. The author proposes by utilizing internet of things (IoT) technology as a means to make it easier for employees and those closest to them to have high awareness of waste. The contribution of this design is based on 3 parties, namely students, PDAM Way Komering and Lampung State Polytechnic. For the design of this final project using the RAD method. With the creation of this system, it can facilitate the management and disposal of waste by officers and the surrounding community.